FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SEKSUAL REMAJA DI DESA MEGAMENDUNG KECAMATAN MEGAMENDUNG KABUPATEN BOGOR PROVINSI JAWA BARAT TAHUN 2016 - Risza Choirunissa; Dewi Kartika Sari (Universitas Nasional, 2017)
Sexual behavior is all behavior driven by sexual desire either do it by himself, opposite sex or the same sex without the bond of marriage according to the religion,Sarwono (2013). The purpose of this study was to determine the factors related of adolescent sexual behavior, of education, knowledge, resources, understanding of religion, the role of the family, in the VillageMegamendung Bogor. Researches with the variables of cross-sectional design with the population of 250 people and a sample of 154 respondents using simple random sampling technique. Based on the results of research we done in the VillageMegamendung, we get the results of risky adolescent sexual behavior with 88 respondents (57.1%). And significant relationship between behavior teen sexual witheducation p value (0.049), resources p value (0.005), understanding of religion p value (0.000), and the role of family p value (0.010) and not significant related between knowledge with behavior teen sexual p value (0,868). We get the results healthy and suggest that young people in the village must get attentionfrom adults, especially sexual behavior problems.